2005
DOI: 10.1354/vp.42-3-315
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Thyroid Transcription Factor-1 Immunohistochemical Staining in the Differential Diagnosis of Primary Pulmonary Tumors of Dogs

Abstract: Abstract. In a previous study, we characterized the reactivity of monoclonal antibody (MoAb) 8G7G3/1 to thyroid transcription factor-1 (TTF-1) in canine thyroid tumors. In this study, we have examined the reactivity of this antibody in 120 canine pulmonary tumors, including 78 primary epithelial tumors. Tissues had been fixed in formalin and routinely processed for histopathology. Nuclear staining for TTF-1 was detected in 64.2% of primary pulmonary epithelial tumors. The most common TTF-1-reactive tumor types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1
13

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 39 publications
(95 reference statements)
5
41
1
13
Order By: Relevance
“…The lung is one of the main sites of metastases and, it is often difficult to distinguish primary pulmonary tumors from metastasis (7,11). In our case, the absence of lesions in other organs corroborates that the neoplastic lesion is primary of the lung.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The lung is one of the main sites of metastases and, it is often difficult to distinguish primary pulmonary tumors from metastasis (7,11). In our case, the absence of lesions in other organs corroborates that the neoplastic lesion is primary of the lung.…”
Section: Discussionsupporting
confidence: 80%
“…TTF-1 is a protein originally identified in follicular cells of the thyroid, but was also found in respiratory cells and areas of the developing brain (7). TTF-1 has been described as a highly specific marker in lung adenocarcinomas in human and dog (7,11). D'Costa et al, (2) showed a labeling specificity of 66.7% in feline lung tumors and it was the highest percentage when compared with other antibodies Surfactant A (SP-A) (50%), Epidermal growth factor receptor (EGFR) (20.8%) and p53 (25%), suggesting the importance of these protein as marker to support the diagnosis of pulmonary tumors in the cat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of immunoreactivity in other neoplasms that would be included in the differential diagnosis (e.g., oral spindle cell sarcomas). 46,48,50,53 iii. Comparison of immunoreactivity between nonneoplastic and neoplastic tissues (antigen expression may be lost or expressed de novo in the neoplastic phenotype).…”
Section: Cross-reactivitymentioning
confidence: 99%
“…20 Its prevalence in retrospective studies is variable: 0/40 (0%), 7 18/218 (8.2%), 10 33/210 (15.7%), 11 or 2/120 (1.6%). 13 This variability is probably because of the fact that several previously reported cases were actually malignant histiocytosis, a neoplasm with similar histologic features: round cells with abundant eosinophilic or foamy cytoplasm and the presence of multinucleated giant cells. 3 Large-cell carcinomas have not been well characterized, in contrast with other uncommon pulmonary tumors, such as adenosquamous carcinoma 15 and small-cell carcinoma.…”
mentioning
confidence: 99%